2014
DOI: 10.2105/ajph.2013.301811
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Social Network Communities and Health Behavior: An Observational Sociocentric Network Study of Latrine Ownership in Rural India

Abstract: Objectives. We identified communities of interconnected people that might serve as normative reference groups for individual-level behavior related to latrine adoption. Methods. We applied an algorithmic social network method to determine the network community from respondent-reported social ties of 16 403 individuals in 75 villages in rural Karnataka, India; data were collected from 2006 to 2008. We used multilevel modeling to test the association between latrine ownership and community-level and village-lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
39
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 56 publications
(42 citation statements)
references
References 51 publications
3
39
0
Order By: Relevance
“…Community-level social connectedness, as measured by several network structure characteristics, may exert different effects on various outcomes across different network types (Alatas et al, 2012; Cai et al, 2012; Entwisle et al, 2007; Shakya et al, 2014b; Zelner et al, 2012). For example, one study in China showed that take-up of weather insurance among rice-farming households was much greater in villages where households were clustered together.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Community-level social connectedness, as measured by several network structure characteristics, may exert different effects on various outcomes across different network types (Alatas et al, 2012; Cai et al, 2012; Entwisle et al, 2007; Shakya et al, 2014b; Zelner et al, 2012). For example, one study in China showed that take-up of weather insurance among rice-farming households was much greater in villages where households were clustered together.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, the same study showed that villages with less internal cohesion displayed more connections to outside villages and exhibited lower fertility and greater affluence. Likewise, a study of latrine ownership in India demonstrated that households were more likely to own a latrine in less cohesive network communities (Shakya et al, 2014b). Finally, a study in Indonesia showed that people in more networked villages were better at identifying which community members were poor than people in less networked villages (Alatas et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent work has shown that when we consider the relationship between networks and behavior it is not simply the relationships between pairs of individuals that should be of interest, but we must also consider the structure of the network itself (Shakya et al, 2014, 2015). The ability for behaviors to change, diffuse, and become established within a community can greatly affect how that community is connected.…”
Section: Resultsmentioning
confidence: 99%
“…They have been tied to a number of health-related outcomes (such as reductions in anxiety and depression (Rajandram et al 2011)). Within social support research in India, normative daily interactions (such as fetching water) were found to be significant sources of social support for women (Shakya, Christakis, and Fowler 2014;Snell-Rood 2015). Similarly, participants in this study described normative daily interactions with street vendors and service industry workers as affirming a positive worldview.…”
Section: Discussionmentioning
confidence: 58%